Continuous caudal analgesia as a safe and effective method for pediatric post - chordectomy analgesia - Senapathi, Tjokorda Gde Agung; Subagiartha, I Made; Widnyana, I Made Gede; Kurniyanta, Putu; Ryalino, Christopher; Estrada, Ronald (DiscoverSys Inc., 2019)
ABSTRACTIt brings great satisfaction for medical officers to be able to see children smiling, laughing, and playing without pain after surgery, yet many children still experience inadequate postoperative pain management. This phenomenon could lead to serious immediate and long term effects in the pediatric patient. Disruption of the healing process caused by pain could become the source of morbidity and mortality in the early postoperative period. Opioid side effects and transformation from acute to chronic pain due to inadequate analgesia are other problems met when dealing with postoperative pain management. This is where regional analgesia takes advantage. Caudal analgesia is an old yet very popular method in pediatric anesthesia and has gained widespread use. It can be delivered as a single injection or continuous infusion. The continuous technique provides a longer duration of analgesia than single injection does. We report a satisfying result from using continuous caudal analgesia for post chordectomy pain management in a 5-year-old boy.